Coupled thermodynamic and experimental approach to evaluate ettringite formation in a soil stabilized with fluidized bed ash by-product: A case study. (June 2020) - Akula, Pavan; Little, Dallas N.
Abstract: Coal combustion by-products, "ash" in various forms have been used extensively to stabilize soils partially due to their relatively slow rate of hydration, pozzolanic reactions and competitive price compared to portland cement. This paper is based on a case study where fluidized bed ash was used to stabilize a subgrade soil causing extensive ettringite formation that resulted in significant structural distress. A total of 45 samples were collected for X-ray diffraction (XRD) and X-ray Fluorescence (XRF) testings. The ash contained up to 70% gypsum, which triggered formation as much as 30% ettringite in a matrix of approximately 94% soil and 6% fluidized bed ash by-product by mass. The Thermodynamic modeling code GEMS-PSI was used to evaluate the occurrence of ettringite and, more specifically, to quantify the extent of ettringite formation. The model is shown to be 91% reliable in its ability to predict ettringite (qualitatively). The quantitative evaluation of the mass percentage of ettringite formation are shown to have a mean error of 12.4% with a standard deviation (SD) of 12.8%. The results from thermodynamic model were calibrated to account for the assumptions that reduced the mean error to 0.12% (SD 4.3%). The results validate the application of the model as a forensic tool. In addition, phase diagrams were developed to graphically illustrate effect of amorphous silica on ettringite formation. They show significant reduction in the stability field of ettringite with an increase in concentration of amorphous silica. The limitations of the model due to incomplete mineralogical data are discussed and a strong case is presented for substantial improvement in the efficacy and quantitative accuracy of the model upon the attainment of more precise mineralogical data.